STUDI MODEL SISTEM PENYERAP TENAGA GELOMBANG LAUT JENIS SILINDER OSILASI TERPASANG TETAP (FIXED OWC) - MUHAMMAD ALI (Inersia: Jurnal Teknik Sipil, 2009)
Indonesia as archipelagic country have more than 3700 island and coastal region as long as 80.000 or twice travel around the world through equator ( Triatmodjo, 1996). Indonesia have very long coast and potency of wave energy  big sea. Energy wave sea can be permeated with system of Oscilating Water Column ( OWC). System OWC represent exploiting of energy wave sea by using column of oscilating. Problems which significan in exploiting of appliance of OWC for water pump is increasing oscilating sea water. Ever greater oscilating sea water o sea hence is ever greater of yielded pump debit.  At this article, research the studied is design of  a model OWC with its tabletop made is open. Later;Then model to be put down in wave channel and treated with variation of depth water,  high and period wave sea.  The Result of examination on model of fixed OWC without wave concentration  and  without reflektor yield value of Ka between 1,05 till 1,23 for the d / gT2 between 0,02 till 0,062. Coefficient value of maximum amplification that is Ka = 1,23 reached at d/gT2 = 0,062. For deepness which remain to indicate that maximum Ka happened  at smallest period. After result of examination of model with wave concentration and without reflektor, assess maximum amplifikasi happened at value of Ka = 1,4 for the value of d/gT2 = 0,052. While to model with wave concentration and use reflektor, assess maximum amplification happened at value of Ka = 1,4 for the d/gT2 = 0,04